Re-thinking Public Health Education in Aotearoa New Zealand: Factory Model to Personalized Learning - Conn, Cath; Nayar, Shoba; Williams, Margaret Hinepo; Cammock, Radilaite (Frontiers in Education, 2021)
Key drivers of change in the 21st century—pandemic, technology advance, social disparity—are shaping the public health industry, including employment and education. In 2020, COVID-19 brought rapid change to the teaching of public health in higher education. In this reflective essay, we move beyond the delivery of existing curricula shifting from classroom to online, and consider the greater agenda of a transformative educational paradigm. This is broadly conceptualized as a shift from a ‘factory model education’ to one of ‘personalized learning’ with an emphasis on fostering creativity and heutagogical (student-driven) models, underpinned by technology, and real world application involving problem and project-based learning in a changing industry. Such change has stemmed both from the impact of COVID-19 on the education system, and in response to a more momentous transformation in public health careers and societal expectations of a public health workforce.